1970
DOI: 10.1192/bjp.116.535.615
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and Clinical Problems of Lithium Prophylaxis

Abstract: Prophylactic maintenance treatment with lithium presents a number of features not shared by conventional therapies. Patients suffering from recurrent affective disorders are offered the possibility of avoiding further psychotic episodes (Baastrup and Schou, 1967; Angstet al.,1970), but the treatment also makes demands on doctors and patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
2
1

Year Published

1973
1973
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(41 citation statements)
references
References 17 publications
1
37
2
1
Order By: Relevance
“…Matussek and Hassling [12] have indicated that tremor is related to increases in lithium gradient and high lithium levels. This is in contrast to Schou [16] who found that 53% of 100 patients exhibited tremor in the 1st month of treatment as opposed to a 4% incidence of tremor after 1-2 years of treatment. Other investigators noted that nausea and abdominal pain were related to greater changes in lithium levels [1,2] while others found no relation between these side effects and blood level [9], Recently, Persson [13] found tremor associ ated with higher lithium levels and greater changes in lithium levels.…”
Section: Discussioncontrasting
confidence: 53%
“…Matussek and Hassling [12] have indicated that tremor is related to increases in lithium gradient and high lithium levels. This is in contrast to Schou [16] who found that 53% of 100 patients exhibited tremor in the 1st month of treatment as opposed to a 4% incidence of tremor after 1-2 years of treatment. Other investigators noted that nausea and abdominal pain were related to greater changes in lithium levels [1,2] while others found no relation between these side effects and blood level [9], Recently, Persson [13] found tremor associ ated with higher lithium levels and greater changes in lithium levels.…”
Section: Discussioncontrasting
confidence: 53%
“…Each of them reported, under different circumstances, that some manic patients who responded to lithium and continued on it remained free of further manias and depressions; a dramatic change compared to the patients' previous histories. Schou and Baastrup [20][21][22] then pursued these reflections systematically and the rest is history. The stabilizing treatment of bipolar disorder with lithium was born, along with many thousands of responders.…”
Section: The Next Stepsmentioning
confidence: 99%
“…Schou et al . (20) reported that about 53 percent of patients showed lithium tremor within the first week of treatment. This was not a demonstrable finding in our stud y.…”
Section: Discussionmentioning
confidence: 99%